Can Cosplay in Story-Telling Improve Student’s Listening Skill in Listening to Stories Learning? - Valiant, Diksi (International Conference on Elementary Education, 2020)
The purpose of this study is to know whether cosplay in story telling can improve students' listening skills. Listening is one of the very important part of a language lesson. Listening is one of the essential skills that will become the foundation of other language developments. Listening skill will affect the ability to speak, read, and write. Therefore listening skills need to be taught to students in elementary school level. One of the obstacles in listening learning, especially stories, is the difficulty of maintaining the student's concentration range. Therefore, a special strategy is needed to increase students' concentration when listening to a story. In an observation at school, a teacher looks "dressed up" uniquelly, which turns out to be one of the characters in the story he delivered in class. It is no exaggeration to call it Cosplay, what the teacher does. Even though it’s not also a perfect one. By dressing-up like a character in the story that is conveyed, children become more interested and grow their interest in learning. Students are also not easily bored. Furthermore, storytelling with Cosplay also provides its own learning experience for students